2019
DOI: 10.3889/oamjms.2019.811
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flexibility, Microstructure and Elemental Analysis of Some Contemporary Nickel-Titanium Rotary Instruments

Abstract: BACKGROUND: Contemporary nickel-titanium (NiTi) rotary endodontic instruments had a revolutionary impact on the success of root canal treatment. AIM: To evaluate the flexibility, microstructure and elemental analysis of four different recent NiTi rotary instruments, namely; Wave One Gold, TF adaptive, HyFlex EDM and Gr_Reciproc Blue compared to conventional Protaper Universal (F2). MATERIAL AND METHODS: The NiTi rotary files were subjected to cantilever bending test to evaluate their flexibility. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…Despite this, only recently has attention been focused on the combined interaction of these two phenomena [ 16 ]. Previously, there was a tendency to consider flexural and torsional stresses as two distinct factors, not considering their reciprocal influence [ 18 , 19 , 20 , 21 , 22 ]. Nevertheless, first Seracchiani et al recently demonstrated the relationship between the torsional resistance of NiTi rotary instruments and the bending moment acting on them, stating that when increasing the flexural loading, the torsional resistance of the bent instruments increases as well.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, only recently has attention been focused on the combined interaction of these two phenomena [ 16 ]. Previously, there was a tendency to consider flexural and torsional stresses as two distinct factors, not considering their reciprocal influence [ 18 , 19 , 20 , 21 , 22 ]. Nevertheless, first Seracchiani et al recently demonstrated the relationship between the torsional resistance of NiTi rotary instruments and the bending moment acting on them, stating that when increasing the flexural loading, the torsional resistance of the bent instruments increases as well.…”
Section: Discussionmentioning
confidence: 99%
“…En la Figura 1C se observan algunas lĂ­neas sobre la superficie del instrumento (Purayil et al, 2018;Gavini et al, 2018). Sin embargo, al comparar mediante el anĂĄlisis de EDX el porcentaje de NiTi de ambos grupos, no se observĂł una diferencia estadĂ­sticamente significativa (p > 0.05) lo cual nos hace suponer que a pesar de que los instrumentos no pasaron por el mismo control de calidad en cuanto al pulido, la composiciĂłn es muy similar entre ambos grupos (Hamdy et al, 2019).…”
Section: Discussionunclassified
“…This finding may be attributed to the metallurgical composition of the file which is based in their fabrication on the transformation of austenite NiTi wire into the Rphase by thermal procedure (De Arruda Santos et al 2013). Moreover, the twisting of the file give a unique shape that improve file flexibility (Walid 2017;Hamdy et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it influences the possibility of endodontic file separation (Fukumori et al 2018). Modifications of the flexibility of the NiTi endodontic rotary instruments depend greatly on their metallurgical composition, fabrication procedure, manufacturing treatment, and geometrical design (He and Ni 2010;Hamdy et al 2019;Galal and Hamdy 2020). Cantilever bending test is the most frequently used test to evaluate the flexibility of the endodontic rotary instruments (Fukumori et al 2018).…”
Section: Introductionmentioning
confidence: 99%